Catalytic, theoretical, and biological investigations of ternary metal (ii) complexes derived from l-valine-based Schiff bases and heterocyclic bases - Gopalakrishnan Sasikumar; Annadurai Subramani; Ramalingam Tamilarasan; Punniyamurthy Rajesh; Ponnusamy Sasikumar; Salim Albukhaty; Mustafa K. A. Mohammed; Subramani Karthikeyan; Zaidon T. Al-aqbi; Faris A. J. Al-Doghachi; Yap, Taufiq Yun Hin (Molecular Diversity Preservation International, 2023)
A new series of ternary metal complexes, including Co(II), Ni(II), Cu(II), and Zn(II), were synthesized and characterized by elemental analysis and diverse spectroscopic methods. The complexes were synthesized from respective metal salts with Schiff’s-base-containing amino acids, salicylaldehyde derivatives, and heterocyclic bases. The amino acids containing Schiff bases showed promising pharmacological properties upon complexation. Based on satisfactory elemental analyses and various spectroscopic techniques, these complexes revealed a distorted, square pyramidal geometry around metal ions. The molecular structures of the complexes were optimized by DFT calculations. Quantum calculations were performed with the density functional method for which the LACVP++ basis set was used to find the optimized molecular structure of the complexes. The metal complexes were subjected to an electrochemical investigation to determine the redox behavior and oxidation state of the metal ions. Furthermore, all complexes were utilized for catalytic assets of a multi-component Mannich reaction for the preparation of -amino carbonyl derivatives. The synthesized complexes were tested to determine their antibacterial activity against E. coli, K. pneumoniae, and S. aureus bacteria. To evaluate the cytotoxic effects of the Cu(II) complexes, lung cancer (A549), cervical cancer (HeLa), and breast cancer (MCF-7) cells compared to normal cells, cell lines such as human dermal fibroblasts (HDF) were used. Further, the docking study parameters were supported, for which it was observed that the metal complexes could be effective in anticancer applications.